Viral Mimicry of Interleukin-17A by SARS-CoV-2 ORF8 - Wu, Xin; Xia, Tian; Shin, Woo-Jin; Yu, Kwang-Min; Jung, Wooram; Herrmann, Alexandra; Foo, Suan-Sin; Chen, Weiqiang; Zhang, Pengfei; Lee, Jong-Soo; Poo, Haryoung; Comhair, Suzy A. A.; et al. (Mbio, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection triggers cytokine-mediated inflammation, leading to a myriad of clinical presentations in COVID-19. The SARS-CoV-2 open reading frame 8 (ORF8) is a secreted and rapidly evolving glycoprotein. Patients infected with SARS-CoV-2 variants with ORF8 deleted are associated with mild disease outcomes, but the molecular mechanism behind this is unknown. Here, we report that SARS-CoV-2 ORF8 is a viral cytokine that is similar to but distinct from interleukin 17A (IL-17A) as it induces stronger and broader human IL-17 receptor (hIL-17R) signaling than IL-17A. ORF8 primarily targeted blood monocytes and induced the heterodimerization of hIL-17RA and hIL- 17RC, triggering a robust inflammatory response. Transcriptome analysis revealed that besides its activation of the hIL-17R pathway, ORF8 upregulated gene expression for fibrosis signaling and coagulation dysregulation. A naturally occurring ORF8 L84S variant that was highly associated with mild COVID-19 showed reduced hIL- 17RA binding and attenuated inflammatory responses. This study reveals how SARSCoV- 2 ORF8 by a viral mimicry of the IL-17 cytokine contributes to COVID-19 severe inflammation.
CRIS-Team Scopus Importer:2022-05-13
Keywords: COVID-19; inflammation; viral IL-17